Are you willing to pay the price? The impact of corporate social (ir)responsibility on consumer behavior towards national and foreign brands. Issue 1 (14th September 2016) - Ferreira, Aristides I.; Ribeiro, Inês
Abstract: This research examines how the country of origin (national vs . foreign) affects the relation between corporate social responsibility (CSR) and consumers' willingness to pay and purchase intention. In the study, we adopted a first‐price sealed bid auction approach, using money in a "real‐world" setting. The results showed that CSR/corporate social irresponsibility (CSIR) affects consumer behavior and, particularly, consumers' willingness to pay and purchase intention. The study supports both the moderation hypothesis of country of origin in the relationship between CSR/CSIR and willingness to pay and between CSR/CSIR and purchase intention. In the globalization context, these results have important implications for brands' communication and marketing strategy and can stimulate important insights in organizations. Future research directions and limitations are also discussed. Copyright © 2016 John Wiley & Sons, Ltd.